POLITIK REGULASI PESANTREN: STUDI ATAS PERPRES NO. 82 TAHUN 2021 TENTANG PENDIRIAN LEMBAGA PENDIDIKAN KEAGAMAAN - Fata Fata (Yayasan An-Nur Meunara Baro, 2025)
This article analyzes the political dimensions of pesantren regulation, focusing on Presidential Regulation (Perpres) No. 82 of 2021 on Pesantren Funding. Using a qualitative policy analysis approach through policy network and critical discourse analysis, this study explores how power relations among the state, Islamic organizations, and pesantren communities are articulated in the policy formulation and implementation processes. The findings indicate that the Perpres is the result of compromises among various actors with differing interests, including the Ministry of Religious Affairs, the Ministry of Education and Culture, and major Islamic organizations such as Nahdlatul Ulama and Muhammadiyah. However, the regulation also reveals bureaucratic tendencies that may undermine the autonomy of pesantren, particularly traditional and salafiyah-based institutions. Theoretically, this policy challenges the classical separation between state and civil society in Islamic education and raises debates on education as a public or private good. Looking ahead, successful implementation requires a more collaborative approach that is sensitive to the local wisdom of pesantren. This article recommends a co-regulation model between the state and pesantren, along with affirmative protections for traditional pesantren, to preserve the diversity of Islamic educational systems in Indonesia.